Unit power rating balancing for differential-power-processing-based distributed photovoltaic systems - Jiahua Ni; Zhixing Zhao; Yinxiao Zhu (Frontiers in Energy Research)
Differential power processing (DPP) architectures are effective solutions for photovoltaic (PV) systems experiencing uncertainties in environmental conditions, such as non-uniform irradiation, which can significantly degrade electricity production efficiency and operating safety. Among the different architectures available, the PV-to-bus DPP configuration has shown excellent performances for control flexibility and galvanic isolation capability. However, recent control schemes for PV-to-bus architectures offer lower-than-desirable efficiency enhancements, such as those involving implementation complexities and unit power distributions. Hence, a unit power rating balancing (UPRB) scheme is proposed in this work to reconfigure the distribution of differential power among the unit converters with the aim of ensuring submodule-level optimization and enhanced performance of the entire PV system. The proposed UPRB scheme integrates perturbation-and-observation-based maximum power-point tracking units to maximize the energy harvested from PV modules, and the unit balance-point tracking unit is employed to determine the optimal string current reference directly for mitigating the unbalanced differential power in the DPP units. By suppressing the maximum processed power in each DPP unit, the capital cost and system size can be reduced. Simulation and experimental studies were conducted, whose evaluation results support the applicability of the proposed control scheme.